Amazon.com, Inc. : the Zappos data crisis - Hanson, Anne; Kenney, Kathleen; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
On January 15, 2012, Zappos, an Amazon subsidiary, was the victim of a purposeful hacking attack. CEO Tony Hsieh sent out a tweet, alerting customers that the systems had been penetrated and directing them to a letter with incident details and recommended customer actions. Given that security breaches have become an increasing concern due to the amount of data stored online, the public immediately criticized Zappos, and a class action lawsuit was filed. Tony Hsieh, and parent company CEO, Jeff Bezos, must decide if any additional payment is due to customers and how to retain brand equity and customer security going forward.
Originally published: Hanson, A., Kenney, K., & ORourke, J. S. (2012). Amazon.com, Inc.: The Zappos data crisis. 12-01. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Zappos.com (Firm); Corporate image; Customer relations; Electronic commerce